Any Second-Line Therapy for Advanced Pancreatic Cancer? Highlights from the '2010 ASCO Gastrointestinal Cancers Symposium'. Orlando, FL, USA. January 22-24, 2010 - Li, Jia; Merl, Man Yee; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Majority of pancreatic cancers are unresectable upon diagnosis. Palliative chemotherapy is usually administered in an attempt of prolonging survival potentially and providing quality of life. Gemcitabine has been the solo player in the field of pancreatic cancer treatment after replacing 5-FU since 1997. How to treat a patient with advanced pancreatic cancer failing to respond or progressing after gemcitabine is a true challenge. No established second-line treatment exists yet. Chinese herbal medicine PHY906 provides cytoprotective effects without dampening the anti-tumor activity of chemotherapeutic agents. Several combinations such as S-1/gemcitabine, GTX, FOLFIRINOX showed promising results in retrospective studies. Among single agents, erlotinib and Src inhibitor failed to show seemingly benefit, while abraxane and pemetrexed deserve further investigation. Image: Yale Cancer Center. New Haven, CT, USA.